(3x-4)/9+x=(3x+4)/3+1

Simple and best practice solution for (3x-4)/9+x=(3x+4)/3+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-4)/9+x=(3x+4)/3+1 equation:



(3x-4)/9+x=(3x+4)/3+1
We move all terms to the left:
(3x-4)/9+x-((3x+4)/3+1)=0
We add all the numbers together, and all the variables
x+(3x-4)/9-((3x+4)/3+1)=0
We calculate fractions
x+(9x-12)/()+(-((3x+4)*9)/()=0
We calculate terms in parentheses: +(-((3x+4)*9)/(), so:
-((3x+4)*9)/(
We multiply all the terms by the denominator
-((3x+4)*9)
We calculate terms in parentheses: -((3x+4)*9), so:
(3x+4)*9
We multiply parentheses
27x+36
Back to the equation:
-(27x+36)
We get rid of parentheses
-27x-36
Back to the equation:
+(-27x-36)
We get rid of parentheses
x+(9x-12)/()-27x-36=0
We multiply all the terms by the denominator
x*()+(9x-12)-27x*()-36*()=0
We add all the numbers together, and all the variables
x*()+(9x-12)-27x*()=0
We get rid of parentheses
x*()+9x-27x*()-12=0
We add all the numbers together, and all the variables
9x+x*()-27x*()-12=0
We move all terms containing x to the left, all other terms to the right
9x+x*()-27x*()=12

See similar equations:

| 7(c-94)=35 | | 30000=2y-3 | | -2(2+11)=b | | 4q+2=34 | | n-53/9=4 | | 9(k-96)=18 | | 7(b-90)=56 | | u/9+79=88 | | z/4+4=8 | | 6x-35+3x+54=180 | | 2=n/4-1 | | 9x-6x+4=x-6+10 | | -3/8y=48 | | 4(x+5)-9=2x+2(4+x) | | (x+7)÷5=13 | | 9y+5y=15 | | x-1,2=3,5 | | (X+3)+(8x+3)=x | | x+0.7x=238000 | | -3(6x-1)+5=-18x+8 | | 6/12=v/10 | | 3x-15+x=25+2x | | (4+v)(2v+1)=0 | | x+5x=12x | | 4x+1/4=x/6+6 | | 2x-6x-14=-4x+9-14 | | x2-2x-120=0 | | 648x+4647=6474 | | 4d+46=7-19 | | 19x-4=21 | | 5.25-0.34x=5x-1.425 | | 5x•30=900 |

Equations solver categories